Being together or apart? Social networks and notions of belonging among recent Polish migrants in the Netherlands - Sabina Toruńczyk-Ruiz (University of Warsaw, Centre of Migration Research (CMR), 2008)
This paper is based on an anthropological study carried out in the Netherlands among recent Polish migrants. The aim of the research was to outline how the Poles experience their stay in the Netherlands and how they develop social networks and notions of belonging. The gathered data show a complex picture of migrant networks: on the one hand Polish networks within small groups of friends and family do play an important role, but on the other - those networks do not tend to connect together and hence do not create a local community among the newcomers. Poles from outside the circle of closest persons are often treated with distance and even distrust, which allows to conclude that a community based on ethnic ties does not emerge. Meanwhile, Polish migrants in the Netherlamds seem to establish a fairly small number of contacts with the host residents and tend to distance themselves from the Dutch as well as other migrant groups. While appreciating their stay in the Netherlands, they also miss many elements of the Polish culture, are proud of qualities that they view as Polish and often see Poland as their final destination, which shows strong ambiguity in the way the migrants view themselves and their own ethnic group.
Keywords: 330; Soziales Netzwerk; Migranten; Polen (Personen); Niederlande